Effects of coastal topography on physiology, behaviour and genetics of indigenous (Perna perna) and invasive (Mytilus galloprovincialis) mussels - Nicastro, Katy R (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2008)
Organisms inhabit environments that have many dimensions, each of which can vary temporally and spatially. The spatial-temporal variations of environmental stressors and disturbances may have major but different effects on indigenous and invasive species, favouring either of them at different times and places. The invasive mussel Mytilus galloprovincialis invaded the South African coast 30 years ago and, on the south coast of South Africa, it now competes and co-exists with the indigenous Perna perna in the lower eulittoral zone (referred to here as the mussel zone) The invasive and indigenous species dominate the upper and the lower mussel zones respectively, while the two co-exist in the mid-zone. My results show that intertidal mussels experience, and respond to, spatial and temporal fluctuations of several biotic and abiotic stressors. The invasive and the indigenous species adopt different strategies when reacting to environmental factors and their physiological and behavioural responses vary in time and in different habitats as different pressures become of overriding importance. Attachment strength of both species decreased in summer and increased in winter, and was higher on the open coast than in bays for both species, showing a strong positive correlation with wave force in time and space. P. perna had significantly higher attachment strength than M. galloprovincialis but, contrary to previous studies, the difference in gonad index between the two species varied according to the habitat. In bay habitats, M. galloprovincialis had a higher maximum reproductive effort than P. perna, however, on the open coast, there was no significant difference between the two species, suggesting that for the invasive species wave action is a limiting factor not only in terms of the attachment strength but also of energy availability for reproductive tissue development. Major spawning events occurred during periods of low wave action while minor spawning coincided with periods of intense hydrodynamic stress. On the open coast, gonad index was negatively correlated with attachment strength for both species while, in bays, there was no correlation between these two factors for either. The two species also showed different behaviour. In the field, M. galloprovincialis moved significantly more than P. perna over a period of six months. The higher mobility of the invasive species was also confirmed in the laboratory where, in general, M. galloprovincialis formed clumps more readily than P. perna. Taken collectively, these results suggest that channelling more energy into attachment strength limits reproductive tissue development and that, while the indigenous species invests more in byssal production, the invasive species adopts a more dynamic strategy looking for aggregation or a safer arrangement. Higher endolithic infestation and a greater expression of heat shock proteins (Hsps) in mussel populations on the open coast than in bays indicate that this habitat is a more stressful environment not only in terms of wave action. Endolith damaged mussels had significantly lower attachment strengths and condition indices than clean mussels, probably due to the need to channel energy into shell repair. The constant shell repair and expression of Hsps typical of open coast populations are energetically demanding processes. These observations suggest that on the open coast, mussels are subjected to more severe energetic constraints than in bay habitats. Wave and sand stress fluctuated seasonally with the former having a greater effect on mussel mortality on the open coast and the latter a higher impact on bay populations. Overall, mussel mortality rates were higher on the open coast than in bays. My results show that populations on the open coast had fewer private haplotypes and less genetic endemism than those inside bays. Gene flow analysis showed the relatively stable bay habitats act as source populations with greater genetic migration rates out of bays than into them. These differences in genetic structure on scales of las of kilometers show that coastal configuration strongly affects selection, larval dispersal and haplotype diversity. Environmental gradients that are key factors in species distribution over large geographical scales can also be responsible for micro-scale distributions. My results show that M. galloprovincialis colonizes the upper mussel zone where temperature is high, but is less tolerant to this stressor and has to maintain a high expression of Hsps. This suggests that temperature is probably a limiting factor in its invasion towards the sub-tropical east coast. There are inter- and intra-specific differences in responses to the environment which highlight the efforts of M. galloprovincialis and P. perna to optimize resource utilization for survival and reproduction. Determining these differences is crucial to understanding patterns of co-existence between competing indigenous and invasive species.
Keywords: Mussels -- Ecology -- South Africa; Perna -- Physiology -- South Africa; Perna -- Behavior -- South Africa; Mussels -- Behavior -- Environmental factors -- South Africa; Mussels -- Habitat -- South Africa; Mytilus galloprovincialis; Mytilus galloprovincialis -- Physiology -- South Africa; Mytilus galloprovincialis -- Behavior -- South Africa; Mytilus galloprovincialis -- Genetics -- South Africa; Coastal ecology -- South Africa